Active Paths to Sustainability: Unlocking Mobility in University Students - Mikiki, Foteini; Katartzi, Ermioni; Oikonomou, Andreas (Scientific Research, New Technologies and Applications Vol. 6, 2024)
Aims: This study aimed at investigating behavioral aspects related to sustainability mobility practices in a specific target group, known for being physically active: the students of the Physical Education and Sport Science Department in Serres, Northern Greece. This work aimed to shed light on gender differences in weekly physical activity levels, as well as gender’s respective effect on mobility practices. Study Design: It was a cross-sectional study, using a tested research instrument, grounded on the Theory of Planned Behaviour within a specific population group. Place and Duration of Study: Data were collected during the first semester of the academic year before the outburst of the COVID-19 pandemic and the restrictive measures imposed by governments. University students filled in the questionnaires once during a typical academic week. Methodology: 259 students from first year to nearing graduation from the Department of Physical Education and Sport Science in Serres, a medium-sized Greek city which is active in mobility issues, filled in a questionnaire, based on Ajzen’s theory of planned behavior and Godin–Shephard Leisure Time Physical Activity Questionnaire for reporting physical activity weekly uptake. Results: The results confirmed higher levels of physical activity in male students, although their attitude towards physical activity was less positive than that of their female classmates. Further positive attitudes in women were recorded towards sustainable mobility choices, although the evidence demonstrated a similar gap between the answers of the two genders. Car possession was higher in men, whereas car purchase intention was slightly lower in women, who had a lower income in general. Moreover, income impacted gender mobility preferences. Conclusion: University student mobility research calls for behavioral approaches to ground relevant interventions. Recommendations can be guided by students’ sports preferences and can be gender-sensitive, taking income into account. The findings could provide implications for policy and practice, informing strategies for promoting sustainable mobility among students.